1981
DOI: 10.1159/000123213
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Morning Melatonin Injections on the Antigonadotrophic Effects of Afternoon Melatonin Administration in Male and Female Hamsters

Abstract: Male and female hamsters were maintained on a long photoperiod (14L:10D) and were divided into the following groups: group 1, injected with vehicle at both 11.00 and 17.00 h; groups 2–5, injected with various doses of melatonin at 11.00 h (0, 100 μg, 500 μg, 1 mg) and 25 g of melatonin at 17.00 h. In males, a.m. vehicle p.m. melatonin treatment for 70 days led to atrophy of the testes and accessory sex organs and to a significant depression of both plasma LH and PRL titers. There was a graded inhibition of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

1983
1983
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 23 publications
1
5
1
Order By: Relevance
“…The data are, in principal, well in accor dance to previously described experiments [1, 4-6, 8, 9, 12, 14, 15, 17, 19, 22-25, 27, 28]. It is generally believed that the duration of melatonin synthesis is the main factor responsible for the physiological effects of short-day photoperiods [3,4,7,15,[22][23][24]. However, other the ories exist which take into account that similar melatonin patterns in hamsters, exposed to a similar photoperiod, may induce opposite effects depending on the lighting conditions the animals were initially exposed to.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The data are, in principal, well in accor dance to previously described experiments [1, 4-6, 8, 9, 12, 14, 15, 17, 19, 22-25, 27, 28]. It is generally believed that the duration of melatonin synthesis is the main factor responsible for the physiological effects of short-day photoperiods [3,4,7,15,[22][23][24]. However, other the ories exist which take into account that similar melatonin patterns in hamsters, exposed to a similar photoperiod, may induce opposite effects depending on the lighting conditions the animals were initially exposed to.…”
Section: Discussionsupporting
confidence: 84%
“…by daily collection of vaginal smears). In the Syrian hamster, there is evidence indicating sexual dimorphism in response to melatonin on reproductive organs [2,24], In the present study the effects of changes in photoperi ods were investigated in female Djungarian hamsters. In particular, comparisons of the diurnal profiles of melato nin synthesis as well as the profiles of its main precursor, serotonin, and 5-hydroxyindole acetic acid (5-HIAA), a metabolite of serotonin, were studied.…”
Section: -| a C Y C Licmentioning
confidence: 96%
“…It is also possible that the contradictory findings in the current study may be due to modulation of the pituitary hormone prolactin caused by experimental conditions as observed by other investigators [29] which might have a different effect on immature and mature prostate glands.…”
Section: Discussioncontrasting
confidence: 58%
“…In such a case no storage takes place and a concentration peak is absent. This may explain the findings of Tamarkin et al (1976Tamarkin et al ( , 1977, Reiter et al (1976), and Richardson et al (1981) who found gonadal atrophy in hamsters kept under long photoperiods (LD 14 : 10) when the animals were injected with aMT just before the beginning of the dark period. At this time never a high concentration of aMT in the pineal was found.…”
Section: Discussionmentioning
confidence: 82%